Fluorescent probes in estimating the transmembrane potential changes of individual cells under effect of adrenaline - Kavok, N. S.; Stepanenko, A. M.; Borovoy, I. A.; Malyukina, M. Y. (Biophysical Bulletin, 2008)
The absolute values and amplitude of transmembrane potential changes in response to adrenaline have been determined in isolated rats hepatocytes by using fluorescent probe H 510 (3,3-diethiloxacarbocyanine bromide). The investigations have been carried out by the microfluorimetry method. The optimum images have been obtained on dyeing the cells with a probe of the minimum concentration 106 M. The transmembrane potential value was estimated at equilibrium probe concentrations from the fluorescence intensity of individual cells after proper digital processing of the photos by using a corresponding application package. To evaluate the potential values the Nernstian formula was adapted for the cationic fluorescent probes. The absolute value of transmembrane hepatocyte potential estimated was in the range of -48.3±6.9 mV. Adding the FCCP (250 нM) did not affect the value obtained (-46.4±2.7 mV), whereas the incubation of the cells in the potassium medium decreased the potential (-30.2±3.7 mV). The above data points that the parameters estimated present the absolute value of the transmembrane potential of the plasmatic hepatocyte membrane. Estimation of transmembrane potential changes from the fluorescence characteristics has revealed two phases of cellular reaction: ((140 мМ К+ ) depolarization by the 5th minute of adrenaline (10-6M) action on the cells and hyperpolarization by the 30th minute of the experiment at +10.3±2.55 mV and -10.0±1.83 mV, respectively. The hyperpolarization effect has not been also found under exposure to phenylephrine (10-6M) which confirms the need for activation of β-adrenoreceptors in order to realize the hyperpolarization hormone action. The data points to the high sensitivity of the carbocyanine probes used to the transmembrane potential changes